Microelectrophoresis of Washed and Unwashed Human Blood Platelets, with Additional Studies of Platelets from Patients with von Willebrand’s Disease and Thrombasthenia - Zucker, Marjorie B; Levine, Richard U (Thrombosis and Haemostasis, 1963)
Microelectrophoretic mobility of washed platelets suspended in isotonic saline or citrated plasma was — 0.75 and — 1.03 (µ/sec.)/(volt/cm) respectively. Erythrocytes traveled about one-third faster. There was no difference between the mobility of unwashed and washed platelets. Mobility of platelets was normal in von Willebrand5s disease. Both mobility and isoelectric point were normal in thrombasthenia.